Abnormal B-Cell Maturation and Increased Transitional B Cells in CBL Syndrome - Francesco Saettini; Tiziana Angela Coliva; Francesca Vendemini; Marta Galbiati; Cristina Bugarin; Riccardo Masetti; Daniele Moratto; Marco Chiarini; Fabiola Guerra; Fabiola Guerra; Maria Iascone; Raffaele Badolato; et al. (Frontiers Media S.A., 2022)
CBL syndrome is a Noonan-like RASopathy with heterogeneous clinical phenotype and predisposition to juvenile myelomonocytic leukemia (JMML). Here we describe two patients with identical germline CBL mutation and clinical and immune-hematological overlapping features with autoimmune lymphoproliferative syndrome (ALPS) and B-cell expansion with NF-κB and T-cell anergy (BENTA) syndrome. Increased immature/transitional B cells can be depicted in CBL syndrome, ALPS, and BENTA. Nonetheless, our patients here described showed peculiar B-cell phenotype due to increased immature/transitional CD34+ B cells. This feature differentiates CBL syndrome from BENTA, pointing toward an abnormal proliferation of B-cell early precursors.